Avaliação neuropsicológica pré e pós deep brain stimulation (DPS) em pacientes com doença de parkinson - Borges, Karina Kelly (2016)
Introduction: Parkinson's disease (PD) is a chronic progressive disease that affects physical, cognitive and emotional aspects. Objective: The aim of this study was to evaluate the occurrence of changes in cognition and symptoms of mental disorders pre and post implant DBS (Deep Brain Stimulation) through a Neuropsychological Assessment (NA). Casuistics and Method: This is a descriptive study in which patients with PD, candidates and submitted to implantation of DBS have participated. NA was performed in these patients before and after implantation of DBS with the following instruments: Wechsler Adult Intelligence Scale; Trail Making Test - Form A and B; Stroop Test; Boston Naming Test; Hooper Visual Organization Test; Wechsler Memory Scale-Revised (WMS-R); Rey Complex Figure; Rey Auditory Verbal Learning Test (RAVLT); Wisconsin Card Sorting Test (WCST) and Beck´s Depression and Anxiety Inventory . Results: From the 29 patients evaluated; the mean age was 60.2 (± 9.35) years , mainly males (n = 19), married (n = 21), with complete primary education (n = 22) and retired ( n = 24). The average time of diagnosis was 11.37 years (± 5.47), the mean age of onset 48.63 (± 7.36). The stage of PD was light to moderate. Clinical evaluation showed significant differences pre and post DBS, with improvement in symptoms. The NA has identified improvement after DBS overall intelligence quotient (p = 0.0022), in activities related to processing speed, and symptoms of mental disorders: depression (p <0.0001), anxiety (p = 0.0038) and apathy (p <0.001). Worsening after DBS was Identified in executive function, memory and verbal fluency. Conclusions: After DBS implantation, there was improvement in symptoms of depression, anxiety and apathy. In general, there was no improvement in cognitive function.